2021
DOI: 10.1111/ibi.12925
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and heart rate responses to stressors in two populations of Little Penguins that differ in levels of human disturbance and predation risk

Abstract: Species that are constantly exposed to disturbances, such as human disturbance or nonlethal contacts with predators or conspecifics, can experience chronic stress. Within a species range, variation in the frequency and predictability of such disturbances can lead to population differences in stress responses. Here, we investigated the stress response of Little Penguins Eudyptula minor to an introduced predator and a conspecific at two South Australian colonies that differed in habitat, conspecific density, lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 112 publications
(132 reference statements)
1
12
0
Order By: Relevance
“…Each track began with 45 min of silence to allow individuals to recover from the deployment of the equipment. Both Larcombe (2016) and Schaefer and Colombelli-Négrel (2021) showed that little penguin heart-rate values returned to baseline levels within half an hour of deployment; hence, we are confident that this interval was sufficient. The 45 min of silence included periodic short bursts (of 1 s) of environmental noises (noises caused by the wind and the ocean and obtained from previous recordings, played at ~65 dB at 1 m every 5 min) to prevent the iPod from shutting down.…”
Section: Playback Experimentsmentioning
confidence: 72%
See 3 more Smart Citations
“…Each track began with 45 min of silence to allow individuals to recover from the deployment of the equipment. Both Larcombe (2016) and Schaefer and Colombelli-Négrel (2021) showed that little penguin heart-rate values returned to baseline levels within half an hour of deployment; hence, we are confident that this interval was sufficient. The 45 min of silence included periodic short bursts (of 1 s) of environmental noises (noises caused by the wind and the ocean and obtained from previous recordings, played at ~65 dB at 1 m every 5 min) to prevent the iPod from shutting down.…”
Section: Playback Experimentsmentioning
confidence: 72%
“…For each tested nest, the sex of the adult penguin present in the nest was confirmed using photographic identification, as previously described for little penguins (Colombelli-Négrel and Smale 2018; Wasiak 2020; Schaefer and Colombelli-Négrel 2021); the fact that the bird was incubating eggs (and not sitting on young chicks) was also established. A dummy egg was then added to the clutch without removing any of the natural eggs to record their physiological response (heart rate) following Schaefer and Colombelli-Négrel (2021). The dummy egg contained an internal omnidirectional lavalier condenser microphone (WL183, Shure Inc., USA) connected to either a Zoom H4n (Zoom North America, USA) or a Tascam DR-05 (TEAC Corporation, USA) as described in Schaefer and Colombelli-Négrel (2021).…”
Section: Playback Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated exposure to acute stressors can change physiological set points and lower the threshold at which physiological mediators start to act pathologically (see homeostatic overload [4]), paralleling effects of chronic stress and making individuals more vulnerable to other prospective stressors [19]. Repeated capture stress makes little penguins ( Eudyptula minor ) react more strongly to subsequent stressors [20] and penguins from a high-disturbance colony give stronger heart rate responses to predator cues [21]. Further, evidence is accumulating that not only the ability to trigger an appropriate stress response is an essential survival mechanism, but also the ability to switch off the stress response when the threat has passed (e.g.…”
Section: Introductionmentioning
confidence: 99%